Strategi Komunikasi Komunitas Kajian Rutin Muslimah dalam Melakukan Kegiatan Dakwah di Masjid Ar-Raudhah Bagan Batu Kabupaten Rokan Hilir Riau - Melisa Afriani Nst; Ahmad Tamrin Sikumbang; Tengku Walisyah (Maktabatun: Jurnal Perpustakaan dan Informasi, 2022)
This study aims to determine the communication strategy of the Muslimah Routine Study Community in carrying out da'wah activities at the Ar-Raudhah Bagan Batu Mosque, Rokan Hilir Regency, Riau and what are the supporting and inhibiting factors of the Muslimah Routine Study community communication planning. This research uses a descriptive method approach. This study uses data collection techniques by means of interviews, observation, and documentation. Informants in this study amounted to six people. Data analysis was carried out by referring to Miles Haberman's opinion, namely data reduction, data presentation and drawing conclusions. The results of the research conducted in this study show: first the communication planning carried out by the Muslimah Routine Study Community is very good, especially in terms of outreach to the public to want to take part in the activities or studies being carried out, create Arabic language learning programs, learn tajwid beginners, learn Iqra and improve Koran reading, practice bathing in jenajah, protect those who have just moved so that they remain istiqomah and open donations for those in need. In the planning of da'wah, each of the elements of da'wah has its own role, namely the competent preacher, mad'u who is the object of da'wah, effective methods, material according to needs, and media that helps in the spread of da'wah. Both in planning there are supporting and inhibiting factors. Utilizing social media facilitates da'wah activities by using gadgets so that they can be accessed easily. The influence of weather and busyness hampered da'wah activities so that it was constrained to attend the activities carried out.